Nano C-S-H crystal nucleus early strength agent and preparation method thereof
By using nano C-S-H crystal core premature strength agent in cement-based composite materials, combining co-precipitation method and preferred polyether monomer types, designing the acid ether molar ratio and introducing early strength functional monomers, the existing premature strength is solved. The alkali aggregate reaction and shrinkage cracking problems of the agent have achieved significant early strength and stability improvement of cement-based composite materials.
Patent Information
- Application Number
- CN202411534401.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
AI Technical Summary
While the existing early strength of cement-based composites increases the early strength of cement-based composites, there is a risk of alkali aggregate reaction and shrinkage cracking. The excessive amount of conventional polycarboxylic acid water reducing agents will affect the retarding effect of cement hydration, resulting in Early intensity increases are not significantly or decreases.
NanoC-S-H crystalline core premature strength agent is used to prepare nanoC-S-H particles by co-precipitation method, and comb polycarboxylic acid polymer is added during the preparation process to improve the steric steric resistance of the particles. Using preferred polyether monomer types and molecular weights, a dispersant with an acid ether molar ratio of (8-13): 1 was designed, and early-strength functional monomers acrylamide and N,N-dimethylaminoethyl methacrylic acid were introduced. ester, a dispersant that forms a microcrosslinked structure.
It significantly improves the early strength of cement-based composites, has good stability, is low dispersant dosage, has a small retarding effect, and does not affect the development of later strength.
Smart Images

Figure BDA0005111208440000091 
Figure BDA0005111208440000101 
Figure BDA0005111208440000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete admixtures, and in particular to a nano CSH crystal nucleus early strength agent and a preparation method thereof. Background Art
[0002] In recent years, in order to meet the fast-paced requirements of industrial development, the engineering community has continuously researched and developed new materials and technologies to improve the early strength of cement-based composite materials. For example, low-temperature construction and the production of precast concrete components often use steam curing or early strength agents to promote the rapid development of the early strength of cement-based composite materials. However, steam curing will not only cause "thermal damage" to concrete, but also increase carbon emissions and energy consumption, which is not conducive to environmental protection; and traditional early strength agents mainly based on inorganic (chloride, sulfate, nitrite, silicate) early strength agents and organic (triethanolamine, calcium formate, urea) early strength agents can improve the early strength of cement-based composite materials, but there is a risk of alkali-aggregate reaction and shrinkage cracking, resulting in a decrease in the later strength of cement.
[0003] Research has found that adding nanocrystalline seed materials to cement-based composites can provide additional nucleation sites for CSH gel, a cement hydration product, and reduce the nucleation barrier of CSH gel, thereby accelerating cement hydration and effectively improving the early mechanical properties and durability of cement-based composites. Synthetic nanoscale hydrated calcium silicate (xCaO·ySiO2·zH2O, CSH) has similar chemical components to CSH gel, the main hydration product of cement, and is an ideal nucleation matrix for cement hydration products. It can significantly improve the early strength of cement-based composites without affecting the development of later strength. It has great application potential in low-temperature construction, repair and rescue, and the production of prefabricated components.
[0004] The coprecipitation method for preparing nano CSH particles is a technical solution that has been widely studied in recent years. In the process of preparing nano CSH, adding comb-shaped polycarboxylic acid polymer can greatly increase the steric hindrance between nano CSH particles. 2+ Complexation, effectively preventing Ca 2+ With SiO3 2-The collision probability of nano-CSH particles is reduced, the growth rate of the crystal nucleus is reduced, and the particle size of CSH is reduced, thereby improving the stability of nano-CSH. During the experiment, it was found that the higher the concentration of nano-CSH particles, the more obvious the improvement of the early strength of concrete under the same dosage conditions. However, when the concentration of nano-CSH particles increases, the amount of conventional polycarboxylate water-reducing agent used as a dispersant must also be increased accordingly to effectively prevent the sedimentation of CSH particles. However, the introduction of excessive dispersants has an adverse effect on the application of early strength agents. Its retarding effect on cement hydration seriously affects its early strength development, resulting in the situation where the prepared nano-CSH does not significantly improve or even reduces the early strength of concrete. Summary of the invention
[0005] Based on the technical problems existing in the background technology, the present invention proposes a nano CSH crystal nucleus early strength agent and a preparation method thereof.
[0006] The present invention provides a nano CSH crystal nucleus early strength agent, comprising the following raw materials in parts by weight:
[0007] 100-150 parts of dispersant, 300-400 parts of water, 10-20 parts of NaOH aqueous solution, 0.1-1 part of defoaming agent, 200-400 parts of Ca(NO3)2·4H2O aqueous solution, 150-350 parts of Na2SiO3·5H2O aqueous solution.
[0008] Preferably, the dispersant is a polycarboxylate water reducer, comprising the following raw materials in parts by weight: 300-450 parts of polyether, 300-450 parts of water, 3-15 parts of NaOH aqueous solution, 1-5 parts of catalyst, 3-10 parts of oxidant, 100-300 parts of monomer A, and 100-200 parts of monomer B.
[0009] More preferably, the polyether is one or more of isopentenyl polyethylene glycol ether, vinyloxyethyl polyethylene glycol ether, and methylallyl polyethylene glycol ether, and the molecular weight of the polyether is 3000-6000, preferably 4000-5000.
[0010] More preferably, the monomer A comprises 40 to 80 parts of acrylic acid, 80 to 120 parts of water, 1 to 3 parts of a chain transfer agent, 3 to 6 parts of acrylamide, and 5 to 10 parts of N,N-dimethylaminoethyl methacrylate.
[0011] More preferably, the molar ratio of acrylic acid to polyether in the monomer A is (8-13):1, preferably (9-12):1.
[0012] More preferably, the chain transfer agent is selected from one or more of mercaptopropionic acid, thioglycolic acid or mercaptoethanol.
[0013] More preferably, the monomer B comprises 0.5 to 2 parts of a reducing agent and 100 to 120 parts of water.
[0014] More preferably, the reducing agent is selected from one or more of vitamin C and diatomaceous earth.
[0015] More preferably, the mass fraction of NaOH in the NaOH aqueous solution is 30-50 wt %.
[0016] More preferably, the catalyst is a 0.05-1.5 wt % ferrous sulfate heptahydrate aqueous solution.
[0017] More preferably, the oxidant is selected from one or more of hydrogen peroxide and ammonium persulfate.
[0018] More preferably, the mass fraction of the hydrogen peroxide is 20 to 50 wt %.
[0019] Preferably, the method for preparing the dispersant comprises the following steps:
[0020] S1. Add water and polyether to the reaction kettle in sequence, stir and dissolve, add NaOH aqueous solution to adjust the pH to 9-11, then add catalyst and oxidant and mix evenly to obtain a mixture; mix acrylic acid, water, chain transfer agent, acrylamide and N,N-dimethylaminoethyl methacrylate evenly to form monomer A for standby use; mix reducing agent and water evenly to form monomer B for standby use;
[0021] S2. Add monomer A and monomer B to the mixture at the same time at 5-30° C. After the addition is completed, stir and age to obtain a dispersant.
[0022] Preferably, the mass fraction of the Ca(NO3)2·4H2O aqueous solution is 30 to 60 wt%.
[0023] Preferably, the mass fraction of the Na2SiO3·5H2O aqueous solution is 25-50wt%.
[0024] More preferably, the molar ratio of Ca(NO3)2·4H2O and Na2SiO3·5H2O is (0.8-1.5):1.
[0025] Preferably, the defoaming agent is polyether-modified polysiloxane.
[0026] The present invention also provides a method for preparing a nano CSH crystal nucleus early strength agent, comprising the following steps:
[0027] S1. Add water and dispersant into the reaction kettle in sequence and stir evenly, then add NaOH aqueous solution to adjust the pH to 9-13, add defoamer and stir evenly to obtain a mixed material;
[0028] S2. Under the condition of initial reaction temperature of 25-40°C and high-speed dispersion, Ca(NO3)2·4H2O aqueous solution and Na2SiO3·5H2O aqueous solution are added dropwise to the mixed material at the same time. After the addition is completed, the mixture is stirred and aged to obtain a nano CSH crystal nucleus early strength agent.
[0029] Preferably, in S2, the shear speed of high-speed dispersion is ≥20 m / s.
[0030] The beneficial effects of the present invention are:
[0031] (1) The dispersant of the present invention optimizes the type and molecular weight of the polyether monomer, wherein the polyether is selected from isopentenyl polyethylene glycol ether, vinyloxyethyl polyethylene glycol ether, and methyl allyl polyethylene glycol ether, and the molecular weight is selected from 3000 to 6000, so that the prepared polymer side chain has stronger steric hindrance, which can better stably disperse the nano CSH particles and prevent particle agglomeration.
[0032] (2) The preferred acid-ether molar ratio of the dispersant is (8-13):1. The high acid-ether ratio and the selected polyether side chain length are relatively long, the carboxyl density on the main chain is high, and the calcium ion adsorption is stronger, and the steric hindrance and electrostatic repulsion can be exerted to a greater extent, thereby more effectively inhibiting the agglomeration of nano CSH particles and exerting better dispersibility. Compared with the conventional polycarboxylate water-reducing agent with an acid-ether ratio of (2-6):1, the nano CSH has better stability, lower usage, and less retarding effect on the cementitious material. The prepared nano CSH can more effectively exert the early strength effect.
[0033] (3) The present invention introduces the early-strengthening functional monomers acrylamide and N,N-dimethylaminoethyl methacrylate to copolymerize, provide N atoms, and synergistically exert the early-strengthening effect through the coordination effect.
[0034] (4) In the present invention, N,N-dimethylaminoethyl methacrylate is introduced into the molecular structure of the dispersant, so that the prepared polymer has a micro-crosslinked structure, the branching degree of the polymer is increased, and the steric hindrance ability of the prepared dispersant is stronger, which can more effectively stabilize the nano-CSH particles and increase their stability.
[0035] (5) The nano CSH material prepared by the present invention has a high solid content, a low amount of dispersant, an effective component solid content of more than 20%, and a good early strength effect. The use of the nano early strength material of the present invention has a significant promoting effect on the early strength of shotcrete and prefabricated component concrete before 1 day of age.
[0036] (6) The preparation process of the present invention adopts high-speed dispersion to prevent CSH nanoparticles from agglomerating during the synthesis process, thereby improving the stability of the early strength agent; the initial reaction temperature is 25 to 30° C., which is conducive to the uniformity and fluidity of the prepared early strength agent. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is described in detail through specific embodiments.
[0038] In the following examples and comparative examples, the specific information of the raw materials used is as follows:
[0039] Polyether: Ethyleneoxyethyl polyethylene glycol ether, molecular weight 5000, manufacturer OXAC-605; Ca(NO3)2·4H2O, manufacturer Wanzhong Chemical; Na2SiO3·5H2O, manufacturer Hubei Xinrunde; N,N-dimethylaminoethyl methacrylate, manufacturer Suzhou Hechuang Chemical.
[0040] Example 1
[0041] A nano CSH crystal nucleus early strength agent comprises the following raw materials in parts by weight: 120 parts of a dispersant, 20 parts of a 40wt% NaOH aqueous solution, 0.5 parts of a polyether-modified polysiloxane, 250 parts of a 40wt% Ca(NO3)2·4H2O aqueous solution, 220 parts of a 35wt% Na2SiO3·5H2O aqueous solution, and the balance being water, based on 1000 parts of the total amount of the raw materials.
[0042] The dispersant is a polycarboxylic acid water-reducing agent, which includes the following raw materials in parts by weight: 375 parts of polyether, 375 parts of water, 6.3 parts of 32wt% NaOH aqueous solution, 2.1 parts of 0.5wt% ferrous sulfate heptahydrate aqueous solution, 4.8 parts of 28wt% hydrogen peroxide, 165.96 parts of monomer A, and 113.46 parts of monomer B; wherein monomer A includes 59.46 parts of acrylic acid, 100.4 parts of water, 1.9 parts of mercaptopropionic acid, 4.2 parts of acrylamide, and 8g of N,N-dimethylaminoethyl methacrylate; and monomer B includes 0.96 parts of vitamin C and 112.5 parts of water.
[0043] The preparation method of a dispersant comprises the following steps: adding water and polyether to a reaction kettle in sequence, stirring and dissolving them, and then adding a NaOH aqueous solution, a catalyst and hydrogen peroxide in sequence and mixing them evenly to obtain a mixture; mixing acrylic acid, water, mercaptopropionic acid and acrylamide evenly to form a monomer A for standby use; mixing vitamin C and water evenly to form a monomer B for standby use; and simultaneously dropping monomer A and monomer B into the mixture at 20°C, and after the dropping is completed, stirring and keeping warm at a temperature raised after the reaction is finished to obtain a dispersant.
[0044] The preparation method of the nano CSH crystal nucleus early strength agent comprises the following steps: adding a dispersant, water, a NaOH aqueous solution and a defoaming agent in a reaction kettle in sequence and stirring evenly to obtain a mixed material; under the conditions of an initial reaction temperature of 30°C and a high-speed dispersion shear speed of 20m / s, simultaneously adding a Ca(NO3)2·4H2O aqueous solution and a Na2SiO3·5H2O aqueous solution to the mixed material, stirring and keeping warm, to obtain a nano CSH crystal nucleus early strength agent.
[0045] Example 2
[0046] A nano CSH crystal nucleus early strength agent comprises the following raw materials in parts by weight: 130 parts of a dispersant, 15 parts of a 40wt% NaOH aqueous solution, 0.5 parts of a polyether-modified polysiloxane, 270 parts of a 45wt% Ca(NO3)2·4H2O aqueous solution, 230 parts of a 40wt% Na2SiO3·5H2O aqueous solution, and the balance being water, based on 1000 parts of the total raw material amount.
[0047] The formula and preparation method of the dispersant are the same as those of Example 1;
[0048] The preparation method of the early strength agent is the same as that of Example 1.
[0049] Example 3
[0050] A nano CSH crystal nucleus early strength agent comprises the following raw materials in parts by weight: 140 parts of a dispersant, 10 parts of a 40wt% NaOH aqueous solution, 0.5 parts of a polyether-modified polysiloxane, 290 parts of a 45wt% Ca(NO3)2·4H2O aqueous solution, 250 parts of a 40wt% Na2SiO3·5H2O aqueous solution, and the balance being water, based on 1000 parts of the total amount of the raw materials.
[0051] The formula and preparation method of the dispersant are the same as those of Example 1;
[0052] The preparation method of the early strength agent is the same as that of Example 1.
[0053] Example 4
[0054] A nano CSH crystal nucleus early strength agent comprises the following raw materials in parts by weight: 130 parts of a dispersant, 15 parts of a 40wt% NaOH aqueous solution, 0.5 parts of a polyether-modified polysiloxane, 270 parts of a 50wt% Ca(NO3)2·4H2O aqueous solution, 230 parts of a 35wt% Na2SiO3·5H2O aqueous solution, and the balance being water, based on 1000 parts of the total raw material amount.
[0055] The formula and preparation method of the dispersant are the same as those of Example 1;
[0056] The preparation method of the early strength agent is the same as that of Example 1.
[0057] Example 5
[0058] A nano CSH crystal nucleus early strength agent comprises the following raw materials in parts by weight: 130 parts of a dispersant, 15 parts of a 40wt% NaOH aqueous solution, 0.5 parts of a polyether-modified polysiloxane, 270 parts of a 40wt% Ca(NO3)2·4H2O aqueous solution, 230 parts of a 45wt% Na2SiO3·5H2O aqueous solution, and the balance being water, based on 1000 parts of the total raw material amount.
[0059] The formula and preparation method of the dispersant are the same as those of Example 1;
[0060] The preparation method of the early strength agent is the same as that of Example 1.
[0061] Comparative Example 1
[0062] A nano CSH crystal nucleus early strength agent comprises the following raw materials in parts by weight: 130 parts of a dispersant, 15 parts of a 40wt% NaOH aqueous solution, 0.5 parts of a polyether-modified polysiloxane, 270 parts of a 45wt% Ca(NO3)2·4H2O aqueous solution, 230 parts of a 40wt% Na2SiO3·5H2O aqueous solution, and the balance being water, based on 1000 parts of the total raw material amount.
[0063] The difference between the dispersant and the dispersant in Example 1 is that the monomer A does not contain N,N-dimethylaminoethyl methacrylate, and the other raw materials and proportions remain unchanged; the preparation method of the dispersant is the same as that in Example 1;
[0064] The preparation method of the early strength agent is the same as that of Example 1.
[0065] Comparative Example 2
[0066] A nano CSH crystal nucleus early strength agent comprises the following raw materials in parts by weight: 130 parts of a dispersant, 15 parts of a 40wt% NaOH aqueous solution, 0.5 parts of a polyether-modified polysiloxane, 270 parts of a 45wt% Ca(NO3)2·4H2O aqueous solution, 230 parts of a 40wt% Na2SiO3·5H2O aqueous solution, and the balance being water, based on 1000 parts of the total raw material amount.
[0067] The difference between the dispersant and the dispersant of Example 1 is that the molar ratio of acrylic acid to polyether in the dispersant monomer A is 5:1, and the other raw materials and proportions remain unchanged; the preparation method of the dispersant is the same as that of Example 1;
[0068] The preparation method of the early strength agent is the same as that of Example 1.
[0069] Comparative Example 3
[0070] A nano CSH crystal nucleus early strength agent comprises the following raw materials in parts by weight: 130 parts of a dispersant, 15 parts of a 40wt% NaOH aqueous solution, 0.5 parts of a polyether-modified polysiloxane, 270 parts of a 45wt% Ca(NO3)2·4H2O aqueous solution, 230 parts of a 40wt% Na2SiO3·5H2O aqueous solution, and the balance being water, based on 1000 parts of the total raw material amount.
[0071] The formula and preparation method of the dispersant are the same as those of Example 1;
[0072] The preparation method of the early strength agent is different from that of Example 1 only in that the initial reaction temperature is 15° C., and the other conditions remain unchanged.
[0073] Comparative Example 4
[0074] A nano CSH crystal nucleus early strength agent comprises the following raw materials in parts by weight: 130 parts of a dispersant, 15 parts of a 40wt% NaOH aqueous solution, 0.5 parts of a polyether-modified polysiloxane, 270 parts of a 45wt% Ca(NO3)2·4H2O aqueous solution, 230 parts of a 40wt% Na2SiO3·5H2O aqueous solution, and the balance being water, based on 1000 parts of the total raw material amount.
[0075] The formula and preparation method of the dispersant are the same as those of Example 1;
[0076] The preparation method of the early strength agent is different from that of Example 1 only in that the shear speed of high-speed dispersion is 10 m / s, and the other conditions remain unchanged.
[0077] Comparative Example 5
[0078] A nano CSH crystal nucleus early strength agent comprises the following raw materials in parts by weight: 130 parts of a dispersant, 15 parts of a 40wt% NaOH aqueous solution, 0.5 parts of a polyether-modified polysiloxane, 270 parts of a 50wt% Ca(NO3)2·4H2O aqueous solution, 230 parts of a 30wt% Na2SiO3·5H2O aqueous solution, and the balance being water, based on 1000 parts of the total amount of the raw materials.
[0079] The formula and preparation method of the dispersant are the same as those of Example 1;
[0080] The preparation method of the early strength agent is the same as that of Example 1.
[0081] Table 1 Ingredients of the early strength agent in the embodiments and comparative examples:
[0082]
[0083] Test Example 1
[0084] Evaluation of the stability of nano early strength agent: 1. Take 10mL of the prepared nano CSH crystal core early strength agent in a centrifuge tube with a cap, centrifuge at a speed of 10000r / min for 6min, then take out the centrifuge tube and observe the stratification of the solution. The more sediment at the bottom, the worse the stability of the nano CSH. 2. Place the nano CSH crystal core early strength agent in a 100mL stoppered measuring cylinder and observe the stratification for 1-3 months at room temperature and indoor environment. The test results are shown in Table 2.
[0085] Table 2 Stability test results of the early strength agent in the examples and comparative examples
[0086]
[0087] It can be seen from the data in Table 2 that the nano CSH crystal nucleus early strength agent prepared in Examples 1 to 5 of the present invention has good stability, no precipitation at the bottom after being placed for a period of time, and the state is stable. The dispersant in Comparative Example 1 does not introduce N,N-dimethylaminoethyl methacrylate, and the stability is insufficient. After being placed for 1 to 3 months, precipitates of varying degrees appear at the bottom. The acid ether ratio of the dispersant in Comparative Example 2 is relatively low, resulting in poor dispersion performance, and the stability of the prepared early strength agent is poor, and a more obvious stratification precipitation phenomenon occurs at an early stage. It can be seen from the experimental data of Comparative Examples 3 and 4 that the lower temperature and shear rate lead to insufficient dispersion effect, which in turn affects the stability of the early strength agent. The calcium-silicon molar ratio of Comparative Example 5 is relatively high, and the synthesized nano hydrated calcium silicate particles are unstable and cannot be evenly dispersed in the system, and the stability is poor.
[0088] Test Example 2
[0089] The above-mentioned early strength agent was applied to early strength shotcrete, and its 6h strength, 1d strength and 28d strength were tested. The test results are shown in Table 3.
[0090] Use C30 shotcrete mix ratio (unit: kg / m 3 ): cement: sand: small stone: water: water reducing agent = 480:800:867:173:2.4; the water reducing agent is the polycarboxylic acid high performance water reducing agent (RAWY-101) of Anhui China Railway Engineering Materials Technology Co., Ltd., and the nano early strength agent is 5% of the cementitious material.
[0091] Table 3 Early strength test data in the embodiments and comparative examples
[0092] Dosage Early strength agent 6h strength / MPa 1d strength / MPa 28d strength / MPa blank 0 5.7 17.6 32.5 Example 1 5% 9.2 21.2 35.3 Example 2 5% 9.8 22.3 36.4 Example 3 5% 9.3 20.4 33.5 Example 4 5% 9.0 20.2 33.7 Example 5 5% 8.9 19.5 33.7 Comparative Example 1 5% 7.7 18.6 31.2 Comparative Example 2 5% 2.5 10.4 32.5 Comparative Example 3 5% 6.1 18.7 32.7 Comparative Example 4 5% 6.2 18.4 32.2 Comparative Example 5 5% 5.9 17.9 32.0
[0093] It can be seen from the data in Table 3 that the nano CSH crystal nucleus early strength agent prepared by the present invention is applied to early-strength shotcrete, and has higher 6h strength, 1d strength, and 28d strength, indicating that the nano CSH crystal nucleus early strength agent prepared by the present invention is applied to early-strength shotcrete, which can not only improve the early strength, but also does not affect the development of later strength.
[0094] It can be seen from the data of Comparative Example 1, the embodiment and the blank example that the introduction of N,N-dimethylaminoethyl methacrylate into the molecular structure of the dispersant can not only improve the stability of the early strength agent but also provide N atoms, which can synergistically exert the early strength effect through the coordination effect, thereby further improving the early strength effect of the early strength agent.
[0095] It can be seen from the data of Comparative Example 2 and the blank example that the dispersant itself has a strong water-reducing and retarding effect at a low acid-ether ratio (<8:1), which hinders the early strength effect, so that the early strength is lower than that of the blank sample.
[0096] It can be seen from the data of Comparative Examples 3 and 4 and the embodiment and the blank example that controlling the initial reaction temperature and the shear rate is beneficial to improving the stability of the early strength agent, thereby improving the early strength effect of the early strength agent.
[0097] It can be seen from the data of Comparative Example 5 and the embodiment that nano CSH particles can be prepared only when the calcium-silicon ratio is within a certain range, and the early strengthening effect of CSH particles prepared beyond the range is weak.
[0098] Test Example 3
[0099] The above-mentioned early strength agent is applied to the segment concrete. The segment concrete is a prefabricated component, which is formed by pouring concrete into the formwork and demolding after reaching a certain strength. At present, the steam curing method is mainly used to improve the early strength of concrete, speed up the mold transfer speed, and improve production efficiency. According to the GB / T 50081 standard, its 8h strength (steam curing for 3h, room temperature) and 1d strength are tested, and the test results are shown in Table 4.
[0100] Concrete mix ratio (unit: kg / m 3 ) : Cement: mineral powder: sand: small stone: medium stone: water: water reducer = 382: 68: 748: 224: 898: 130: 1.9. The water reducer is the polycarboxylic acid high performance water reducer (RAWY-101) of Anhui Zhongtie Engineering Materials Technology Co., Ltd., and the nano early strength agent is 5% of the cementitious material.
[0101] Table 4 Early strength test data in the embodiments and comparative examples
[0102]
[0103] It can be seen from the data of the blank and the embodiment that the nano CSH crystal nucleus early strength agent prepared by the present invention is applied to the segment concrete, and has higher 8h strength (steaming for 3h, room temperature) and 1d strength, indicating that the nano CSH crystal nucleus early strength agent prepared by the present invention can be applied to the segment concrete to effectively improve the early strength, especially the early strength of the segment concrete after steaming for 3h has an absolute advantage.
[0104] It can be seen from the data of Comparative Example 1 compared with the examples and the blank examples that N,N-dimethylaminoethyl methacrylate was not introduced into the dispersant, and its early strength effect was weak; compared with the examples and the blank examples, the water-reducing and retarding effect caused by the low acid-ether ratio (<8:1) in Comparative Example 2 still exists.
[0105] It can be seen from the data of Comparative Examples 3 and 4 and the embodiment that lower initial reaction temperature and shear rate will result in larger particle size of the prepared nano-CSH, easy agglomeration, insufficient nano effect, and poor early strength effect.
[0106] It can be seen from the data of Comparative Example 5 and the embodiment that the early strength effect of the nano-CSH prepared when the calcium-silicon ratio exceeds a certain range is insufficient.
[0107] In summary, the nano CSH crystal nucleus early strength agent provided by the present invention can effectively improve the early strength of concrete whether it is applied to early strength shotcrete or segment concrete.
[0108] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A nano CSH crystal nucleus early strength agent, characterized in that: It includes the following raw materials in parts by weight: 100-150 parts of dispersant, 300-400 parts of water, 10-20 parts of NaOH aqueous solution, 0.1-1 parts of defoaming agent, 200-400 parts of Ca(NO3)2·4H2O aqueous solution, 150-350 parts of Na2SiO3·5H2O aqueous solution; the dispersant is a polycarboxylic acid water reducer, which includes the following raw materials in parts by weight: 300-450 parts of polyether, 300-450 parts of water, 3-15 parts of NaOH aqueous solution, 1-5 parts of catalyst, 3-10 parts of oxidant, 100-300 parts of monomer A, and 100-200 parts of monomer B.
2. The nano CSH crystal nucleus early strength agent according to claim 1, characterized in that: The polyether is one or more of isopentenyl polyethylene glycol ether, vinyloxyethyl polyethylene glycol ether, and methallyl polyethylene glycol ether, and the molecular weight of the polyether is 3000-6000; the monomer A comprises acrylic acid, water, a chain transfer agent, acrylamide, and N,N-dimethylaminoethyl methacrylate, wherein the mass ratio of acrylic acid, water, chain transfer agent, acrylamide, and N,N-dimethylaminoethyl methacrylate is (40-80):(80-120):(1-3):(3-6):(5-10); the monomer B comprises a reducing agent and water, wherein the mass ratio of the reducing agent to water is (0.5-2):(100-120); wherein the molar ratio of acrylic acid to polyether in monomer A is (8-13):
1.
3. The nano CSH crystal nucleus early strength agent according to claim 2, characterized in that: The chain transfer agent is selected from one or more of mercaptopropionic acid, thioglycolic acid or mercaptoethanol; the reducing agent is selected from one or more of vitamin C and bleaching agent.
4. The nano CSH crystal nucleus early strength agent according to claim 1, characterized in that: The mass fraction of NaOH in the NaOH aqueous solution is 30-50wt%; the catalyst is a 0.05-1.5wt% ferrous sulfate heptahydrate aqueous solution; the oxidant is selected from one or more of hydrogen peroxide and ammonium persulfate; the mass fraction of hydrogen peroxide is 20-50wt%; and the defoamer is polyether-modified polysiloxane.
5. The nano CSH crystal nucleus early strength agent according to claim 1, characterized in that: The preparation method of the dispersant comprises the following steps: S1. Add water and polyether to the reaction container in sequence, stir and dissolve, add NaOH aqueous solution to adjust the pH to 9-11, then add catalyst and oxidant and mix evenly to obtain a mixture; mix acrylic acid, water, chain transfer agent, acrylamide and N,N-dimethylaminoethyl methacrylate evenly to form monomer A for standby use; mix reducing agent and water evenly to form monomer B for standby use; S2. Add monomer A and monomer B to the mixture at the same time at 5-30° C. After the addition is completed, stir and age to obtain a dispersant.
6. The nano CSH crystal nucleus early strength agent according to claim 1, characterized in that: The mass fraction of the Ca(NO3)2·4H2O aqueous solution is 30-60wt%; the mass fraction of the Na2SiO3·5H2O aqueous solution is 25-50wt%; the calcium-silicon molar ratio of Ca(NO3)2·4H2O and Na2SiO3·5H2O is (0.8-1.5):
1.
7. A method for preparing the nano CSH crystal nucleus early strength agent according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Add water and dispersant into the reaction kettle in sequence and stir evenly, then add NaOH aqueous solution to adjust the pH to 9-13, add defoamer and stir evenly to obtain a mixed material; S2. Under the condition of initial reaction temperature of 25-40°C and high-speed dispersion, Ca(NO3)2·4H2O aqueous solution and Na2SiO3·5H2O aqueous solution are added dropwise to the mixed material at the same time. After the addition is completed, the mixture is stirred and aged to obtain a nano CSH crystal nucleus early strength agent.
8. The preparation method according to claim 7, characterized in that: In the S2, the shear speed of high-speed dispersion is ≥20m / s.
Citation Information
Cited By
Accelerator-free sprayed concrete as well as preparation method and application thereof
CN121270163A
Quick-setting and quick-hardening concrete and preparation method thereof
CN121377687A